Pemberdayaan Ibu Hamil Mengenai Faktor Risiko Kehamilan di Puskesmas Tirto 1 Kabupaten Pekalongan - Suparni Suparni; Wahyu Ersila; Windha Widyastuti (Indonesian Journal Publisher, 2025)
The highest maternal mortality rate in Pekalongan Regency in 2022 was recorded at Puskesmas Tirto 1, with 6 cases (17.64%) of the total cases in the regency. Out of 897 pregnant women in this area, 418 were classified as high-risk (46.60%), with a significant prevalence of anemia, preeclampsia, and malnutrition. This activity aimed to empower 35 pregnant women in two villages through education and training on pregnancy risk factors. The methods used included socialization, educational material delivery, health examinations, and practical risk assessment using the Poedji Rochjati Scoring Card (KSPR). Pregnant women were provided with guidance on pregnancy danger signs and the importance of routine check-ups, which included measuring body weight, height, mid-upper arm circumference (MUAC), blood pressure, and hemoglobin levels. The results indicate active participation from pregnant women who are highly interested in applying the knowledge they gained. An increase of 32.50 points in the mean knowledge score of pregnant women before and after the counseling sessions, measured through a questionnaire, serves as a parameter indicating the effectiveness of the counseling in enhancing their understanding of pregnancy risk factors. Through a demonstration of the KSPR (Pregnancy Risk Screening Card) use, participants were able to independently identify risks. This empowerment aims to raise awareness among pregnant women and the surrounding community about the importance of early detection and monitoring of high-risk pregnancies, which is expected to reduce maternal mortality rates in the region. The conclusion of this activity is that it successfully empowered pregnant women with the knowledge and skills needed to maintain their health during pregnancy, potentially reducing complications and maternal mortality in the region.